2003
DOI: 10.1007/s00122-003-1364-3
|View full text |Cite
|
Sign up to set email alerts
|

Fine linkage mapping enables dissection of closely linked quantitative trait loci for seed dormancy and heading in rice

Abstract: Two quantitative trait loci (QTLs) for seed dormancy (tentatively designated Sdr1) and heading date ( Hd8) have been mapped to approximately the same region on chromosome 3 by interval mapping of backcross inbred lines derived from crosses between the rice cultivars Nipponbare (japonica) and Kasalath (indica). To clarify whether Sdr1 and Hd8 could be dissected genetically, we carried out fine-scale mapping with an advanced backcross progeny. We selected a BC(4)F(1) plant, in which a small chromosomal region in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 29 publications
1
35
0
3
Order By: Relevance
“…Several dormancy QTL regions have been isolated in introgression or near isogenic lines for Arabidopsis, barley, and rice (Han et al, 1999;Alonso-Blanco et al, 2003;Gao et al, 2003;Takeuchi et al, 2003). Fine mapping these regions suggests: (1) a dormancy QTL may consist of a gene cluster (Han et al, 1999); (2) some dormancy QTLs may lose their effect in a nondormant genetic background (Alonso-Blanco et al, 2003); (3) some QTLs are especially sensitive to the environment during seed development (Gao et al, 2003); and (4) an influence of flowering time on dormancy may be due to tight linkage between loci for both traits (Takeuchi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several dormancy QTL regions have been isolated in introgression or near isogenic lines for Arabidopsis, barley, and rice (Han et al, 1999;Alonso-Blanco et al, 2003;Gao et al, 2003;Takeuchi et al, 2003). Fine mapping these regions suggests: (1) a dormancy QTL may consist of a gene cluster (Han et al, 1999); (2) some dormancy QTLs may lose their effect in a nondormant genetic background (Alonso-Blanco et al, 2003); (3) some QTLs are especially sensitive to the environment during seed development (Gao et al, 2003); and (4) an influence of flowering time on dormancy may be due to tight linkage between loci for both traits (Takeuchi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Fine mapping these regions suggests: (1) a dormancy QTL may consist of a gene cluster (Han et al, 1999); (2) some dormancy QTLs may lose their effect in a nondormant genetic background (Alonso-Blanco et al, 2003); (3) some QTLs are especially sensitive to the environment during seed development (Gao et al, 2003); and (4) an influence of flowering time on dormancy may be due to tight linkage between loci for both traits (Takeuchi et al, 2003). Some of the introgression lines were used to estimate geneadditive effects for the QTL.…”
Section: Introductionmentioning
confidence: 99%
“…Takeuchi et al (2003) carried out fine mapping of QTLs for DTH and seed dormancy in this region. Hori et al (2010) detected a QTL for preharvest sprouting that is allelic with qLTG3-1 identified by Fujino et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence that QTL of domestication-related traits are clustered close together on the same linkage group (Koinange et al, 1996;Takeuchi et al, 2003;Gu et al, 2005;Hancock, 2005). In buckwheat, summer ecotype cultivars are considered to have differentiated from the late-summer ecotype cultivars as a result of adaptation to the long-day condition of summer cropping in high latitude regions (Minami and Namai, 1986).…”
Section: Discussionmentioning
confidence: 99%